ANALISIS STRATEGI PENGEMBANGAN BUMDES DALAM PENIGNKATAN PADES PADA MASA PANDEMI COVID-19 (Studi Kasus Pada BUMDES Rukun Makmur Desa Gunungrejo Kecamatan Singosari Kabupaten Malang) - Ferry Prasetyia; Sulistia Wirandini, Dewi Asmia (Journal of Development Economic and Social Studies, 2022)
Covid-19 pandemic has had a negative impact on countries up to villages. One of the impacts on the village is Village Owned Enterprises. Based on data from The Minister of Villages, underdeveloped Regions and Transmigration, in 2021 there were 15,768 Village Owned Enterprises affected by pandemic. Also, the number of inactive Village Owned Enterprises in Indonesia was 12,040. This research was conducted at Rukun Makmur Village Owned Enterprises which has developed status since 2019. In addition, they achieved an award as runner-up of Village Owned Enterprises Award 2020 in a profit category during Covid-19 period. However, they also had several problems that must be resolved on its progress. Thus, this research aims to examine the development of Rukun Makmur Village Owned Enterprises before and during Covid-19 to find out their strategies in overcoming problems, so it can be used as a reference by other Village Owned Enterprises which are less active on their growth and to improve Village Owned Enterprises development in the following years. The research method is a mix method using descriptive analysis techniques and Hierarchy Analysis Process (AHP). The results show that to overcome Village Owned Enterprises problems, the first strategic priority is to increase Human Resources both in quality and quantity, the second is to increase Village Owned Enterprises and village finances, then the third is to increase the village potential  by exploring and making good use of it. So its will improve village own-source revenue.